Carbon and [sup.15]nitrogen isotopes in autopsy liver tissue samples from Greenlandic Inuit and Danes: consumption of marine versus terrestrial food - Milman, N; Laursen, J; Mulvad, G; Pedersen, H.S; Pedersen, A.N; Saaby, H (European journal of clinical nutrition, 2010)
Background/Objectives: The content of [sup.13]C and [sup.15]N isotopes is higher in marine than in terrestrial food. [sup.13]C and [sup.15]N in human tissue therefore reflects the relative proportions of marine and terrestrial food consumed by the individual. The objective of this study was to measure [sup.13]C and [sup.15]N in liver tissue from Greenlandic Inuit and Danes. Subjects/Methods: Normal liver tissue was obtained at autopsy in 1992-1994 from 60 Inuit with a median age of 61 years (range 25-83) and in 1986 from 15 ethnic Danes with a median age of 84 years (range 66-93). By sieving, liver tissue was separated in a 'cellular fraction' and a 'connective tissue fraction'. [sup.13]C and [sup.15]N in dry liver tissue was measured on a mass spectrometer. [δ.sup.13]C indicates the [sup.13]C content relative to the IAEA-CH-6 reference standard. [δ.sup.15]N indicates [sup.15]N content relative to the atmospheric nitrogen reference standard. Results: Inuit: median [δ.sup.13]C was -21.2% in cellular and -20.0% in connective tissue fractions (P = 0.001). Median [δ.sup.15]N was 10.6% in both cellular and connective tissue fractions. Body mass index was negatively correlated with [δ.sup.13]C in the connective tissue fraction ([r.sub.s] = -0.42, P = 0.057). Danes: median [δ.sup.13]C was -27.0% in cellular and -24.3% in connective tissue fractions (P = 0.11). Median [δ.sup.15]N was 9.5% in cellular and 8.9% in connective tissue fractions (P = 0.5). Inuit had higher [δ.sup.13]C than Danes in both cellular and connective tissue fractions (P< 0.001) as well as higher [δ.sup.15]N in the cellular fraction (P = 0.01). Conclusions: Inuit showed considerable variation in the ratio between marine and terrestrial food consumption, reflecting a vanishing hunter culture where elderly Inuit still adhere to the traditional hunters food with a high content of marine food, whereas the younger urbanized Inuit population consume food with a lower content of marine food and a higher content of terrestrial food. Danes consumed food of almost exclusively terrestrial origin. The present [sup.13]C and [sup.15]N analyses are in accordance with the dietary patterns obtained by dietary surveys. European Journal of Clinical Nutrition (2010) 64, 739-744; doi: 10.1038/ejcn.2010.67; published online 2 June 2010 Keywords: [sup.13]carbon; Denmark; Eskimos; Greenland; Inuit; liver; mass spectrometry; [sup.15]nitrogen